Health Maintenance Practices Among Nurses of a Tertiary Level Hospital of Nepal - Shrestha, Shovana; Thakuri, Aastha Singh; Devkota, Rashmi (Journal of College of Medical Sciences-Nepal, 2018)
ABSTRACT Background: Health maintenance practices are those activities that preserve a person’s current state of health and that prevents future diseases or injuries from occurring. Nurses represent an important part of the hospital workforce and serve as role models when caring for patients. A healthy nurse can deliver quality care to the patients to the optimal level. However, there are no studies that explored the health maintenance practices among nurses, here in Nepal. This study was therefore conducted to assess the health maintenance practices among nurses. Materials and Methods: A total of 197 out of 208 nurses from Nepal Medical College Teaching Hospital (NMCTH) were enrolled in the study using purposive sampling method. Pretested questionnaire was used as a tool for data collection. SPSS version 16 was applied for data entry and analysis. Descriptive statistics (Percentage, frequency, mean, standard deviation) were used for data analysis. Results: Among 208 nurses only 197 responded yielding a response rate of 94.7%. The findings suggest that nurses did not have a good screening, dietary, exercise and vaccination practices. Lack of time, work overload, psychological stress from work were the main barriers pointed out by the nurses that hinder them to maintain their health status. Conclusion: Nurses did not have good health maintenance practices which could directly influence on the quality of care they provided. Thus it is very necessary to initiate program that promotes health of nurses. Keywords: health maintenance practice; Nepal; nurses; self care.